Implementasi Peramalan Stok Parfum Pada Imshop Parfum dengan Metode Weighted Moving Average - Nur’aini, Zulfiana; Santi, Nirma Ceisa; Mahmudah, Nur; Barata, Mula Agung (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Humans are social creatures who need to communicate with each other. In this regard, it is necessary to provide comfort in a conversation. To provide this comfort, you can use perfume. Imshop Parfum is a shop that sells various choices of perfume scents, but of the various types of perfumes sold, of course there are perfumes that are the most popular and rarely purchased, this is certainly a problem if the stock of the item runs out or provides too much stock. The purpose of this study is to predict the stock of goods at Imshop Parfum. The method used in this study is the Weighted Moving Average with periods 3 and 5. The forecast results from the perfume study in June 2025 were 215 for period 3, and 212.86 for period 5. MAPE is 1.98% for period 3, and the MAPE value is 2.74% for period 5. It can be concluded that period 3 is the best and most accurate result because it has the smallest MAPE value.